2017
DOI: 10.18203/2320-1770.ijrcog20175285
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal serum vitamin D level with preeclampsia or eclampsia and its relationship with neonatal outcome and neonatal serum calcium level

Abstract: Background: Vitamin D deficiency has been associated with various poor maternal and fetal outcome and is proposed to be important in the pathogenesis of preeclampsia. The aim of the study was to evaluate the serum vitamin-D levels in normal pregnant females and pre-eclampsia or eclampsia individuals in the third trimester admitted for termination or in labour and to assess the neonatal outcome and neonatal serum calcium levels of babies born to mother in both the groups.Methods: This study was a prospective co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…In terms of age, BMI, Mean gestational age there was no difference in the study and control group indicating that they were comparable. Similarly, Sahu M et al (2017) 13 and Goel P et al (2016) 14 observed no significant difference in their age group. Like our study, Goel P et al (2016) 14…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In terms of age, BMI, Mean gestational age there was no difference in the study and control group indicating that they were comparable. Similarly, Sahu M et al (2017) 13 and Goel P et al (2016) 14 observed no significant difference in their age group. Like our study, Goel P et al (2016) 14…”
Section: Discussionmentioning
confidence: 85%
“…(2019), 23 Choudhary N et al (2018), 24 Sahu M et al (2017), 13 Baror S et al (2017), 16 Kumari A et al (2017), 25 Goel P et al (2016), 14 Sadin B et al (2015), 21 Singla et al (2015) 26 and Bakacak et al (2015). 15 Our study also demonstrated that though vitamin D deficiency was common in all antenatal patients but it was significantly more prevalent in preeclamptic women.…”
Section: Variablementioning
confidence: 99%
“…Nearly, 95% and 85% of the women among case and control group respectively were deficient in vitamin D. Similar results were reported by Rimpi Singla et al [9] in their study. Mahija Sahu et al [10] in their study revealed that 75% of the patients in the hypertensive group with either preeclampsia or eclampsia were found to have very severe deficiency (<5 ng/ml) as compared to 25% of those in the healthy normotensive group. Robinson et al [11] carried out a study to assess the levels of total 25-hydroxyvitamin D (25-OH-D) at diagnosis of early-onset severe preeclampsia and found reduced total 25-OH-D levels in comparison to healthy controls (P <0.01).…”
Section: Discussionmentioning
confidence: 95%
“…Sahu et al conducted a similar study where the mean serum vitamin D level was 9.06±5.20 ng/ml in diseased group as compared to 13.67±7.24 ng/ml in healthy pregnant group which was statistically significant (p<0.05) and exactly similar to the present study. 6 Mehta et al conducted a study also concluded vitamin D level is lower in women with HDP as compared to healthy pregnancy women also the level of vitamin D decreases with severity of HDP. 7 Similar to current study, Gupta et al found more incidence of severe vitamin D deficiency (90%) in preeclamptic patients as compared to normotensive patients (62%).…”
Section: Discussionmentioning
confidence: 96%